1993
DOI: 10.1139/e93-147
|View full text |Cite
|
Sign up to set email alerts
|

Postglacial emergence of Ungava Peninsula, and its relationship to glacial history

Abstract: A series of 178 radiocarbon dates, of late glacial and postglacial age, from raised marine terraces on the Hudson Strait, Hudson Bay, and Ungava Bay coasts, permit a new synthesis of deglaciation history, postglacial emergence, and glacio-isostatic recovery of the Ungava Peninsula. Marine limits show three local highs, related to centres of ice loading: east of Hudson Bay; southwest of Ungava Bay, and in western Hudson Strait. Eastward extension of the latter to Cap de Nouvelle-France is attributed to early de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
0
5

Year Published

1998
1998
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(63 citation statements)
references
References 25 publications
4
54
0
5
Order By: Relevance
“…Richard et al (in review) showed by AMS dating of macrofossils that previous conventional radiocarbon dates from the plateau of Gaspé Peninsula are too old and that déglaciation finally occurred after 10 ka BP rather than about 12 ka BP. Payette (1993) and Gray et al (1993) proposed that final déglaciation of the Ungava region of Québec occurred 5.5-5 ka BP, 1 ka later than the date suggested by Dyke and Prest (1987). The younger déglaciation proposal for that area is based on a few basal peat and gyttja dates that Dyke and Prest (1987) regarded as not closely constraining the dates of déglaciation and on a peculiarity in the present distribution of Larix.…”
Section: Paleogeographymentioning
confidence: 96%
See 1 more Smart Citation
“…Richard et al (in review) showed by AMS dating of macrofossils that previous conventional radiocarbon dates from the plateau of Gaspé Peninsula are too old and that déglaciation finally occurred after 10 ka BP rather than about 12 ka BP. Payette (1993) and Gray et al (1993) proposed that final déglaciation of the Ungava region of Québec occurred 5.5-5 ka BP, 1 ka later than the date suggested by Dyke and Prest (1987). The younger déglaciation proposal for that area is based on a few basal peat and gyttja dates that Dyke and Prest (1987) regarded as not closely constraining the dates of déglaciation and on a peculiarity in the present distribution of Larix.…”
Section: Paleogeographymentioning
confidence: 96%
“…A sample placed well inside the ice margin in Hudson Strait consists of unidentified shell fragments from till on Akpatok Island dated at 11.97 ka BP. These apparently record a brief opening of the strait followed by a readvance of ice onto southern Baffin Island (Gray et al, 1993). Foraminiferal and diatom records of cores off Hudson Strait indicate fairly high biological productivity and seasonally open water 12-11 ka BP (Andrews era/., 1990).…”
Section: Molluscan Zones At 11 Ka Bpmentioning
confidence: 99%
“…Les courbes d'émersion disponibles pour le Québec nordique reposent surtout sur la datation de coquillages marins et peu sur des datations de sols enfouis (Gray et al, 1993). Les environnements littoraux sableux récents du lac Guillaume-Delisle sont cependant pauvres en coquillages marins et la courbe d'émersion des terres est basée principalement sur des datations de coquillages, toutes plus anciennes que 4500 années cal.…”
Section: Introductionunclassified
“…Les mollusques analysés sont issus des sédiments marins de la péninsule d'Ungava et des îles adjacentes dont l'exondation glacio-isostatique pendant l'Holocène a été étu-diée par Gray et al (1993). L'objectif était d'établir des courbes d'émersion.…”
Section: Les Mollusques Analysésunclassified
“…Les échantillons de mollusques dont les âges et les valeurs en 8 PDB ' 8 Oont été déterminés furent récoltés au cours des vingt dernières années dans le cadre des recherches sur ! 'emersion postglaciaire de cette région (Gray et al, 1993). Quelques données isotopiques ont déjà été publiées, notamment celles provenant de la côte ouest de la baie d'Ungava (Lauriol et al, 1979 ;Gray et al, 1980).…”
Section: Introductionunclassified